REFORMS IMPLEMENTED IN THE LIVESTOCK SECTOR IN UZBEKISTAN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
As a result of the reforms implemented in Uzbekistan based on the new development strategy, serious attention is being paid to the development of the livestock sector on a multi-pronged basis in order to meet the population’s needs for livestock products. Despite this, the number of livestock and the volume of products, as well as the productivity of livestock, remain relatively low. This article presents opinions on the reforms implemented in the livestock sector in Uzbekistan.